Mapeamento e priorização de fontes de geração distribuída como suporte ao novo planejamento da distribuição - Azzolin, Herton Naressi (2015)
Despite the growing movement of the share of renewable sources in the global energy matrix, the weight of sources such as natural gas, coal and petroleum derivatives is considerably significant. In this respect, the need for diversification of the energy matrix is evident and urgent, mainly due to the growing demand for energy, and requires appropriate planning of the matrix transition process in order to attend the growing demand on a sustainable basis and in a balanced way. Being the Distributed Generation (DG) a viable and real alternative to contribute to this scenario favorably, beyond the amount of intrinsic variables to DG that can impact positively or negatively on the electrical system, the development of methods and tools to support the usual techniques of planning need to be reviewed. In this sense, it is proposed in this study a methodology for mapping and prioritizing of DG sources from renewable resources, to support the new perspective of distribution planning. The focus is given to the wind power, photovoltaic, hydro and biomass, dealt in the current literature as the most promising for diversification of energy sources. The methodology includes the realization of a mapping of available energy resources in an enclosed area for study, indicating the most favorable places of exploitation. Documents already established concerning energy potential, such as atlas and energy balances, are used as reference information for the mapping. Once mapped the resources available, it is estimated the energy capacity that they represent, through methods and equations which consider the main variables to estimate the potential of each source. The methodology also includes a step of prioritization of mapped sources from multiple quantitative and qualitative criteria, to indicate the best form of participation of them in two different perspectives of analysis. The first one under the point of view of electric utilities, with the focus on the potential use to support the system expansion and operation, and the second one from the perspective of investors, aimed at exploitation the potential for expansion of its generation mix. For the multi-criteria approach of prioritizing the sources it is used the Analytic Hierarchy Process (AHP) method. The modeling is applied as a case study from the area of operation of a electric utility in the state of Rio Grande do Sul.